LUBUK IKAN LARANGAN SEBAGAI BENTUK KEARIFAN LOKAL DI KAMPUNG KOTO KANDIS KECAMATAN LENGAYANG KABUPATEN PESISIR SELATAN - Fajar Surya Lestari; Paus Iskarni; yudi Antomi (JURNAL BUANA, 2017)
This study aims to (1) find out the factors affecting Kampung Koto Kandis serve as the prohibition of fish holes and (2) to know the system of local wisdom implementation in the prohibition of fish in Kampung Koto Kandis.The method used in this research is the Mixed Method. Research Samples are taken as many as 15 people and 10 respondents.The result of this research is to find out (1) the factors that influence the area is used as the prohibition of the focus to two factors, namely: the first factor of Koto Kandis society that originated from the thinking, musyawarah, planning, supervision and community cooperation hence formed the fish. Second, the physical condition: Kapalo Banda River is the main river flow and is the first order river because it is not encountered by other river branches, the river flows following the slope of the rock layer, and the topography of the area around the river is dominated by a flat slope.2) The system of local wisdom of fish prohibition in Kampung Koto Kandis accepted and formed in 2007 by people Koto Kandis, people just believe, then provide peace, and food for the fish so that the fish are used to life and do not feel disturbed. it is intended that no people take fish, but in fact this does not use any mystical element.